Business plan of TuRest Co. / Muammad Haiqal Harith Rathi ... [et al.] - Muammad Haiqal, Harith Rathi; Munirah, Abd Majid; Nor Atikah Nadhirah, Kamal Bahrin; Siti Norsyazlin Amiza, Haris; Tengku Suraya Amelin, Tengku Baharudin (2020)
An executive summary is a short document or section produced for the purposes of business. This is an overview of the key ideas in the report. It presents an overview of the purpose, scope, main findings, conclusions and recommendations. TuRest Co. is an organization that offers luxurious, comfortable and affordable tudungs that is focus on the protection of aurat and to please the female muslim audience. Their satisfaction and is our priority. Our market target are the women of islam ranging from mid to low class with our affordable price, However our sophisticated design maybe appealing to those from the upper class. With both high fashion design and amazing comfortability, our tudung maybe of use to any events and occasions. TuRest Co. is based in Taman Kajang Sentral, Selangor but our delivery service extends towards the entirety of Malaysia. With millions of Muslim women residence in Malaysia, the demand of our products have bloomed across the nation. While their maybe many tudung specialty companies in Malaysia, not many offer a unique design such as ours that put an emphasis in covering the neck area, which is a crucial part of the aurat that is often overlooked in most tudung companies. Our organization also puts a heavy concern towards the environment. We carefully plan our operations as to impact as little as possible towards polluting the environment. This is due to the growing concern of pollution, global warming and negative effects it has on the environment from the customers as well as our own. Thus the name TuRest, which is a combination of Tudung and Forest. Our marketing strategy is to emphasize quality over quantity. We offer high quality for an affordable price while still being able to maintain high profits due to our customer care and excellent service. Being favorable quality and affordable, we are able to attract the low income audience who are often struggling as we are able to understand their hardships. The management of TuRest Co. consist of four (4) members whom are Haiqal Harith, Munirah Majid, Atikah Nadh, Syazlin Amiza and Suraya Amelin. Our members are knowledgeable and experience in the field of business, marketing, sales and accounting. Some of our members have personally worked our certain sales and accounting business, and their knowledge and experience have helped us in many ways. Our business operation has extended widely across Malaysia as we have committed towards expanding our business towards more branches namely in Perak, Kelantan and Negeri Sembilan. We are also looking towards attracting more customers via advertising through online, billboards and newspapers.